Symbolic reparation, trauma and victimization: The response of the Chilean State to human rights violations (1973-1990) - Javiera Bustamante-Danilo; Alejandra Carreño-Calderón (Íconos)
More than 30 years have passed since the civil-military dictatorship and few studies have addressed the role the victim category had in the Chilean State’s strategies implemented since 1990 onward to address the human rights violations which took place between 1973 and 1990. Through a documental and ethnographic analysis of symbolic reparation and the norms associated with social and sanitary programs, this article explores how the Chilean State has adminis-tered human rights violations, torture and disappearances based on two principles: the narrative of victimization and the adoption of an individualized perspective to address trauma. Through the analysis of documental and ethnographic material, this research exposes how this treatment has marked the public agenda in terms of human rights. On the one hand, this has made it possible to ignore the demand for clarity regarding the bodies of those who were detained and disappeared. And on the other hand, there has been a lack of recognition of the role the State had in the perpetration of this violence during the civil-military dictatorship. This analysis demonstrates that even though the use of the figure of victim contributed to isolating people who suffered mistreatments and to depoliticize their actions, it is necessary to problematize the potential for collective action of victimhood and its possible dialogues with other contemporary social movements.